Pemanfaatan Sistem Tanam Tumpangsari terhadap Pertumbuhan Vegetatif Dua Kultivar Tanaman Kedelai Hitam (Gylcine Max L) - Gurbas Ida Rohima Hasibuan; Rahmadina Rahmadina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the use of spacing and cultivars for the growth of black soybean plants with an intercropping system (Gylcine max L.). This research method used a factorial randomized block design (RBD) with 2 factorials and 4 replications. Factor I (K) cultivars were K1 = detam 2 soybean cultivar and K2 = detam 4 soybean cultivar. The interval (J) consisted of three levels: J1 = 10 x 20 cm, J2 = 15 x 20 cm, J3 = 20 x 20 cm . The observed variables were plant height, leaf area index, root nodules, relative growth rate (LPR), chlorophyll content, and net assimilation rate (LAB). The results showed that treatment with K2 (detam 4) had a significant effect on plant height 14.28 HST, relative growth rate, chlorophyll a, b and total. The treatment of J1 spacing (10 x 20 cm) had a significant effect on 14 DAP height and leaf area index. Based on the research, it can be concluded that the intercropping system and black soybean cultivar had a significant effect on plant height, relative growth rate, chlorophyll a, b, total, and leaf area index. Keywords: Spacing, Black Soybean, Cultivars, Growth, Intercropping